Detection of shifts in microbial functional gene (nosZ and nifH) distribution due to long term warming of a high Arctic soil. - Walker, Jennifer K. M. (Author); Egger, Keith (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2007)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1309789